A Rapid Detection of Haemophilus influenzae Using Multiple Cross Displacement Amplification Linked With Nanoparticle-Based Lateral Flow Biosensor - Cao, Qilong; Liang, Shaoshuai; Wang, Lin; Cao, Jun; Liu, Mengyang; Li, Shengpeng; Cao, Xiaolong; Guo, Yan (Frontiers in Cellular and Infection Microbiology, 2021)
Haemophilus influenza is a major human pathogenic bacterium, resulting in a series of diseases, such as pneumonia, bacteremia, meningitis. However, it is hard to diagnose H. influenza quickly. In this study, the multiple cross displacement amplification (MCDA) and nanoparticle-based lateral flow biosensor (LFB) (MCDA-LFB) were combined to detect H. influenza, which has been proved to be reliable, rapid, and not complicated. On the basis of H. influenza outer membrane protein P6 gene, 10 specific primers were designed. The best MCDA condition was 61℃ for 1 h. The sensitivity of H. influenza-MCD-LFB assay showed, in the pure cultures, the minimum concentration of genomic DNA templates was 100 fg. The specificity of H. influenza-MCD-LFB assay showed only H. influenza templates were detected, and no cross-reactivity was found in non-H. influenza isolates and other Haemophilus species. In 56 sputum samples, with MCDA-LFB method and PCR detection, 21 samples were positive, which was inconsistant with the traditional culture method. The accuracy of diagnosis of MCDA-LFB, in comparison with the traditional culture method and PCR detection, can reach 100%, indicating that the MCDA-LFB assay gains an advantage over the cultured-based method for target pathogen detection. In conclusion, the MCDA-LFB assay is suitable for the sensitive, rapid and specific detection of H. influenza, which might be used as a potential diagnostic tool for H. influenza in basic and clinical laboratories.